Yield performance of Agro-industrial wastes as substrate for cultivation of Pleurotus florida - Toppo, Swati Rose (Mushroom Research, 2018)
A study was conducted to examine the yield performance of agro- industrial wastes for the cultivation of Pleurotus florida, generated in Bilaspur district of Chhattisgarh in relevance to usage of waste for food production and waste management. Locally available agrowastes such as Wheat straw, Paddy straw, sugarcane bagassae and corn stover were used singly and in combinations, as substrate for mushroom production. Various parameters were examined such as spawn run time (mycelia development), pinhead formation, fruit body formation and yield. The experiments were setup as a randomized design with three replicates. Results revealed that Maize-Stover produced better yield in comparison to wheat straw, paddy straw and sugarcane bagasse for spawn running(15-20 days) and pinhead formation (18-25 days) where as total cropping duration of  Pleurotus florida  was higher in Paddy straw  and Wheat straw+ Maize stover (34 days). Maximum average yield (595.8 grams) with highest biological efficiency of 66.2% was recorded for Paddy straw+ corn stover followed by wheat straw + Maize stover (60.99%).